HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN LANJUT USIA DALAM MELAKSANAKAN SENAM LANSIA DI POSYANDU KONDANG WARAS DESA NGARGOREJO - Muttaqin, Alif Zaenal; Rahayuningsih, Faizah Bety (Universitas Muhammadiyah Surakarta, 2010)
Advanced age is a demographic problem facing the world in the elderly will occur naturally aging process that causes some problem such as physical deterioration of the organs. Elderly gymnastics is one sport that can improve fitness and health of the elderly. The results of observation conducted by researchers at the neighbourhood health center Kondang Waras Ngargorejo Boyolali there are 60 registered of elderly, while active and participacing in gymnastic only 20 elderly or 30% of the population. The purposes of study was to determin the relationships of family support with the level of compliance in implementing the elderly in Posyandu Kondang Waras Ngargorejo Boyolali. The research using quantitative research, descriptive research design correlation. Sample in this study amounted to 50 respondents with data retrieval technique is random sampling. The test statistic using Kendal tau correlation test. Measurement of the respondents regarding family support using a questionnaire. The result showed that the level of family support is less, there are 8 respondents (73%) had not obedient compliance, the next 2 respondents (18%) are less obedient, and a respondent (9%) adherence. At the level of family support is there are 1 respondent (3%) had a compliance doesn’t obey, then 28 respondents (88%) are less obedient, and 3 respondents (9%) adherence. While at the level of good family suppor there is 1 repondent (14%) had not obedient compliance, the next 2 respondents (29%) are less obedient, and 4 respondents (56%) adherence. Based on the distribution of the elderly in terms of level compliance with family support, it appears that the better level of family support, the better level of compliance in perfoming gymnastic elderly.